PENGUJIAN PUPUK DAUN DENGAN GIBERELIN PADA BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) YANG MENGALAMI GENANGAN AIR - Qurrata A’yun; Nurbaiti Nurbaiti; Gunawan Tabrani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This research aims to improve the growth of oil palm seedlings (Elaeis guineensis Jacq.) Which are continuous puddles for 30 days by planting together with giberelin growth regulators. The study was conducted in the Riau Faculty's lithology garden from August to December 2017, in the form of plot design experiments divided by random patterns repeated three times. Main plot: leaf fertilizer concentration (D), consisting of d0: without leaf fertilizer (0 ppm), d1: 1,500 ppm, d2: 3,000 ppm. Subplots in the form of gibberellin concentration (G), consisting of g0: without giberelin (0 ppm), g1: 15,000 ppm, g2: 30,000 ppm. The parameters observed were plant height, number of leaf midribs, tuber diameter, number of adventitious roots, root volume, root canopy ratio, seed dry weight and seed quality index. The results showed that there was no interaction between leaf fertilizer concentration and gibberellin concentration on the growth component of oil palm seedlings which were harvested for 30 days continuously by air inundation. The height of the oil palm seedlings which ignite the inundation continuously for 30 days can be increased as high as 7.47 cm with the administration of giberellin, but cannot improve on other growth components. The application of leaf fertilizer cannot be used to repair oil palm growth with 30 days of inundation, even increasing seed dry weight 47.40 g. Palm oil seedlings that are prolonged stressed inundation, initiate adventitious plant formation. Keywords: Palm oil seedlings, waterlogging stress, foliar fertilizer and gibberellin.